Students’ Worldview Attitude and Education Content Orientation - Bidjiev, Djasharbek U.; Borlakova, Svetlana A.; Klushinа, Nadezhda P.; Petrova, Nina P.; Pivnenko, Petr P.; Uzdenova, Alina A.; Kharchenko, Leonid N. (Journal of History Culture and Art Research, 2017)
The idea of students’ worldview attitude application when forming educational content is proved in the article on the basis of scientific literature. In particular, it is claimed that any natural phenomenon can be comprehended, apparently, two-fold: either through its comparison to other beings or the phenomena, or through disclosure of its own unique nature. For example, studying the person "from the outside", assumes interpretation of the relations good fortune, the nature (space), society (culture), the law and other people. Approach to the secret of the person is accompanied by comprehension of his corporal, emotional, moral, spiritual and social life "from within". In many respects it depends on what methodology will be chosen by the researcher, and, the choice of methodology is connected with worldview attitude of the personality. In the publication definition of worldview attitude is given; briefly the essence of such worldviews as teocentrism, logocentrism, cosmocentrism, sociocentrism, anthropocentrism are revealed, as well as results of pilot study from students’ worldview attitude of higher education institution are presented. The obtained data demonstrate that in student's audience there are young people, with various worldview attitudes that can be used by the teacher in selecting subject content. The variety of approaches and views of natural and social processes and the phenomena allow forming an overall picture of the world in students of higher education institutions.